Asuhan Kebidanan Pada Ibu Nifas Dengan Bendungan Asi Di Pmb Rungkut Surabaya - Neti Dora Tardjo; Fauziah.F.Hernanto; Dewi Purwatiningsih (2025)
Breastfeeding dams are a frequent problem at the beginning of postpartum, which can cause discomfort and thus become one of the barriers to exclusive breastfeeding. Breastfeeding dams are often associated with late onset, lack of breastfeeding, or ineffective breast emptying. The research sample used was 1 (one) postpartum mother with ASI enggorgenent at PMB Rungkut, Surabaya. He continuity of care method is used in running parenting, which is continuous parenting starting from pregnancy, childbirth, niphas to newborns. The solution provided is communication of information and education about the correct breastfeeding position, encouraging mothers to breastfeed on demand, advising mothers to compress cold and nutritious foods. From the provided care results, that is, the difficulty can be detected immediately so that there is no gap between theory and practice and can be solved immediately so that there are no more serious problems.